Place of border cluster and ways of implementation in classification of East Kazakhstan region tourist cluster - Yeshenkulova, G.I.; Gizzatzhanova, A.G.; Kussainova, A.K.; Raiymbekova А.Т. (BUKETOV BUSINESS REVIEW, 2017)
Nowadays, at the stage of development of tourism of Kazakhstan to increase efficiency of socio-economic of tourism service use cluster method . on the basis of preparing clusters are forming unique, exclusive product. creation the core of a tourist cluster in a number of projects take a special place in territorial-geographical region in the border areas of the location. First of all, globalization affect to border area by emerging of tourist projects in the near of border regions. According to the researchers, tourists, near the border formed under the influence of high development potential of cross-border tourism. Features of the cluster approach, methods and prospects of development of tourism and the formation and development of the tourism cluster in the border areas needs a scientific study. In this regard, the country as a its own zone, allowing the development of a cluster of two major cross-border tourism clusters in East Kazakhstan destinations, Katonkaragay National Park and the Nature of the State Nature Reserve is supposed to be offered as a tourist product. Therefore, 2 objects should be combined into one tourist cluster, in order to develop it successfully, in addition to all issues mentioned before we would recommend to use Australian road between Katonkaragay National Park and Nature reserves in the state.